2015
DOI: 10.1097/jto.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

CSF Concentration of Crizotinib in Two ALK-Positive Non–Small-Cell Lung Cancer Patients with CNS Metastases Deriving Clinical Benefit from Treatment

Abstract: W e describe two cases with central nervous system (CNS) metastases from anaplastic lymphoma kinase (ALK)positive non-small-cell lung cancer (NSCLC) that benefited from the ALK-inhibitor crizotinib. In both cases, crizotinib was dosed in serum and corresponding cerebrospinal fluid (CSF) through ultra-high performance liquid chromatography (Agilent Technologies, Santa Clara, CA). 1 CASE 1 A 58-year-old never-smoker with ALK-positive advanced NSCLC pretreated with chemotherapy developed asymptomatic CNS metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 5 publications
2
70
2
1
Order By: Relevance
“…Most small molecule TKIs, including crizotinib [Costa et al 2011;Metro et al 2015], imatinib [Motl et al 2006], gefitinib [Jackman et al 2006] and erlotinib [Clarke et al 2010] have been shown to exhibit low CSF to plasma ratios. Consequently, the CNS is a sanctuary site where ALK+ NSCLC can disseminate [Gainor et al 2013].…”
Section: Secondary or Acquired Resistancementioning
confidence: 99%
“…Most small molecule TKIs, including crizotinib [Costa et al 2011;Metro et al 2015], imatinib [Motl et al 2006], gefitinib [Jackman et al 2006] and erlotinib [Clarke et al 2010] have been shown to exhibit low CSF to plasma ratios. Consequently, the CNS is a sanctuary site where ALK+ NSCLC can disseminate [Gainor et al 2013].…”
Section: Secondary or Acquired Resistancementioning
confidence: 99%
“…The central nervous system (CNS) has been reported to be a frequent site of acquired resistance to crizotinib in patients with ALK-positive NSCLC (26)(27)(28). In the present study, cerebral progression occurred in more patients in the crizotinib group (n=10; 50%) in comparison with those in the chemotherapy group (n=4; 8.5%).…”
Section: Discussionmentioning
confidence: 50%
“…This phenomenon can be largely attributed to the following two reasons: Firstly, crizotinib is a substrate of P-glycoprotein, a membranous transporter overexpressed in the hematoencephalic barrier and responsible for the efflux of the drug. Low cerebrospinal fluid-to-serum ratios have been reported for crizotinib in the range between 0.06 and 0.26% (31,32). Furthermore, crizotinib extended the patient survival, which to a certain extent may be contributed to the higher incidence of CNS metastases as compared with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high tumor activity of these compounds with prolonged control of extra-cranial disease could make emerge CNS as relevant site of progression. This is particularly true for crizotinib, which may inefficiently cross the blood brain barrier thus reaching limited concentration in the cerebrospinal fluid (CSF) (16,101,102). CNS involvement resulted the first site of progression in 46% of ALK-positive patients treated with crizotinib, with 85% of these lacking systemic progression (103).…”
Section: Efficacy Of Alk Inhibitors On Brain Metastasesmentioning
confidence: 99%